2022
DOI: 10.1094/phyto-03-21-0128-r
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Activity ofBacillusspp. andPseudomonasspp. AgainstBotrytis cinereaand Other Cannabis Fungal Pathogens

Abstract: Gray mold caused by Botrytis cinerea is one of the most widespread and damaging diseases in cannabis crops worldwide. With challenging restrictions on pesticide use and few effective control measures, biocontrol agents are needed to manage this disease. The aim of this study was to identify and characterize bacterial biocontrol agents with wide-spectrum activity against B. cinerea and other major cannabis fungal pathogens. Twelve Bacillus and Pseudomonas strains were first screened with in vitro confrontationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 134 publications
0
27
0
1
Order By: Relevance
“…Pseudomonas spp. (Pseudomonadaceae) is one of the most abundant genera of beneficial rhizobacteria among the large and heterogeneous bacterial populations in the rhizosphere and has, therefore, attracted growing attention as a source of potential biological control agents [ 11 , 12 ]. Except for some human pathogenic strains [ 13 ], the species of P. aeruginosa is a versatile and ubiquitous bacterium that has been recognized as an active antagonist of several bacterial and fungal plant pathogens, and has potential practical applications in agricultural systems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas spp. (Pseudomonadaceae) is one of the most abundant genera of beneficial rhizobacteria among the large and heterogeneous bacterial populations in the rhizosphere and has, therefore, attracted growing attention as a source of potential biological control agents [ 11 , 12 ]. Except for some human pathogenic strains [ 13 ], the species of P. aeruginosa is a versatile and ubiquitous bacterium that has been recognized as an active antagonist of several bacterial and fungal plant pathogens, and has potential practical applications in agricultural systems [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, these results were not validated on plants (Afzal et al, 2015;Scott et al, 2018). Ongoing research with other beneficial bacteria and fungi, like Bacillus, Streptomyces, Trichoderma, and/or Gliocladium, further supports the potential of antagonistic biocontrol agents against Botrytis on marijuana inflorescences (Punja and Ni, 2021) and hemp leaves (Balthazar et al, 2021), and against Fusarium and powdery mildew on marijuana stem cuttings and leaves, respectively (Punja, 2021;Scott and Punja, 2021). Besides, various fungal endophytes were also isolated from hemp and marijuana plants previously, but their antimicrobial activities were only tested in vitro (Gautam et al, 2013;Kusari et al, 2013;Qadri et al, 2013).…”
Section: Local Effects Of Pseudomonas Spp Inoculantsmentioning
confidence: 98%
“…Notably, their antagonistic activities can be used to control fungal and bacterial diseases, but also herbivorous insects (Flury et al, 2016;Khan et al, 2016), parasitic nematodes (Trivedi and Malhotra, 2013) and weeds (Trognitz et al, 2016). Accordingly, antibiotic production was suggested as the main antifungal mechanism of beneficial P. protegens and P. synxantha strains when sprayed on hemp leaves to control Botrytis gray mold, and/or inhibiting the in vitro growth of Botrytis, Sclerotinia, Fusarium, Alternaria, and Phoma (Balthazar et al, 2021). Previous studies also demonstrated that two strains of Pseudomonas koreensis and Pseudomonas taiwanensis found in the hemp rhizosphere could inhibit the growth of Aspergillus and/or Fusarium in vitro by producing siderophores, cellulases, pectinases and proteases (Afzal et al, 2015), while hemp endophytes Pseudomonas fulva and Pseudomonas orientalis inhibited the growth of Botrytis, Sclerotinia and/or Rhizoctonia in vitro by producing siderophores, cellulases, and antibiotics (Scott et al, 2018).…”
Section: Local Effects Of Pseudomonas Spp Inoculantsmentioning
confidence: 99%
See 2 more Smart Citations